EVALUASI PROGRAM PRAKTIK LAPANGAN PERSEKOLAHAN DENGAN MENGGUNAKAN MODEL CSE-UCLA - Sidik, Firman; Rasyid, Muhammad Nur Akbar; Mania, Sitti (Irfani, 2023)
This article aims to analyze and evaluate the School Field Practice program. This program evaluation research uses an evaluation model developed by Alkin, namely CSE-UCLA "Center for the study of evaluation University of California in Los Angeles.” The model evaluation consists of 5 evaluation stages, namely: system assessment, program planning, program implementation, program improvement, and program certification. However, in this evaluation the researcher only focused on one component, namely the focus on program planning. The results of the research show that the competence of field supervisors is very good, as well as the tutor teachers who are very competent and professional in carrying out their responsibilities